Tiga Sisi Kepribadian Gelap, Segitiga Kecurangan Dan Niat Korupsi (Studi Empiris Pada Pemerintah Kota X) - Farikhoh, Ilmi; Rohman, Abdul (E-Jurnal Akuntansi; Vol 32 No 8 (2022), 2022)
This study aims to analyze the of personality narcissism, machiavellianism, psychopathy, financial & non-financial pressure, perception of opportunity, and rationalization on corrupt intentions. The population is the Head of Regional Government Organizations (OPD) in Pemkot X with the sampling technique used is census, so the total sample are 50 respondents. In addition, this study also chose variance-based SEM (PLS-SEM) as a data analysis technique. Empirical facts show that machiavellianism, financial and non-financial pressure, and rationalization have a positive influence on the corrupt intentions, while narcissism, psychopathic, and perceived opportunity do not have a positive influence on the corrupt intentions. The results of this study have implications in the development of corruption detection that based on empirical studies individuals make decisions to be involved in fraud scandals, especially corruption is influenced by several factors. Keywords: Personality; Triangle; Fraud; Intention; Corruption